2015
DOI: 10.15406/jbmoa.2015.01.00004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Potential Enteric Pathogens in Treated and Untreated Water Sources around Eastern Cape Region

Abstract: Background: Fecal contamination of water sources has always been a major safety concern and a factor in determining the need of a continuous treatment program. A routine monitoring program for drinking water sources would provide increased public health protection. The aim of this study was to determine the prevalent rates of potential enteric pathogens in water sources in Eastern Cape. Methods: Water samples (from water surfaces and undergrounds) were collected from treated and untreated water sources. The Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The findings of this investigation are in agreement with those of a study conducted in 2022 by Khabo-Mmekoa and colleagues [32], who found that household water samples were mainly contaminated by enteric pathogens such as Salmonella and Shigella. Muringani et al [33] also reported similar findings, showing that 87.5% of all water samples analysed from both treated and untreated sources in their study were contaminated with pathogenic bacteria. The findings of this study will assist water service authorities in rural areas to develop strategies aimed at reducing the exposure of humans to pathogens that cause diseases, and to create an awareness that household factors such as hygiene practices might be responsible for the recontamination of treated water.…”
Section: Discussionsupporting
confidence: 70%
“…The findings of this investigation are in agreement with those of a study conducted in 2022 by Khabo-Mmekoa and colleagues [32], who found that household water samples were mainly contaminated by enteric pathogens such as Salmonella and Shigella. Muringani et al [33] also reported similar findings, showing that 87.5% of all water samples analysed from both treated and untreated sources in their study were contaminated with pathogenic bacteria. The findings of this study will assist water service authorities in rural areas to develop strategies aimed at reducing the exposure of humans to pathogens that cause diseases, and to create an awareness that household factors such as hygiene practices might be responsible for the recontamination of treated water.…”
Section: Discussionsupporting
confidence: 70%